2018
DOI: 10.3390/su10051525
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Tourism in Sensitive Areas: Bibliometric Characterisation and Content Analysis of Specialised Literature

Abstract: Thirty years after the emergence of the term "sustainable tourism" and in view of the proliferation of literature on the subject, it seems appropriate to carry out a bibliographical review, based on empirical bibliometric data, in order to find out who the leading research pioneers are for this type of tourism, discover gaps in our understanding, and redefine the concept's frontiers. This paper focuses specifically on sustainable tourism in sensitive areas, in a first attempt to provide understanding of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
0
29
0
1
Order By: Relevance
“…Thus, this study has two research objectives: (a) to conduct a modernism‐based interpretation of sustainable development and (b) to solicit a modernism‐based understanding or conceptual framework of sustainable tourism. This study is expected to decrease confusion with the concept, thereby enhancing the knowledge about sustainable tourism, one of the most prominent areas in tourism field (Qian et al, ; Sánchez‐Cañizares et al, ). Advanced conceptual understanding and a theoretical framework with summarized thinking may facilitate consistent transformation and thus reduce miscommunication in both academic discussions and practical policymaking (Miller & Twining‐Ward, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, this study has two research objectives: (a) to conduct a modernism‐based interpretation of sustainable development and (b) to solicit a modernism‐based understanding or conceptual framework of sustainable tourism. This study is expected to decrease confusion with the concept, thereby enhancing the knowledge about sustainable tourism, one of the most prominent areas in tourism field (Qian et al, ; Sánchez‐Cañizares et al, ). Advanced conceptual understanding and a theoretical framework with summarized thinking may facilitate consistent transformation and thus reduce miscommunication in both academic discussions and practical policymaking (Miller & Twining‐Ward, ).…”
Section: Introductionmentioning
confidence: 99%
“…The past 30 years have witnessed an exponential increase in research on sustainable tourism (Sánchez-Cañizares, Castillo-Canalejo, & Cabeza-Ramírez, 2018). In 2012, Buckley (2012) estimated that approximately 5,000 studies had been published on this topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research in this topic has grown a lot in recent years (Qian, Shen, & Law, 2018). According to Buckley (2012), a search by this topic in Web of Science showed more than 8,500 results and more than 1 million in Google Scholar (Sánchez-Cañizares et al, 2018). Xiao and Smith (2006) said that, tourism journals have also recognized the importance of such review studies and have published more of these articles.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the paper also indicated that Scopus has a better coverage in the community tourism due to collecting a greater number of articles and journals, and its articles receive a greater number of citations. Finally, the paper of Sánchez-Cañizares et al (2018) conducts a bibliographical review in order to find out who the leading research pioneers are in sustainable tourism in sensitive areas, discover gaps, and to redefine the concept's frontiers.…”
Section: Introductionmentioning
confidence: 99%